Effects of Escherichia coli vaccination in gilts on piglet performance in a farm in Perak - Fong, Michelle Wai Cheng; Choo, Pow Yoon; Ong, Bee Lee; Tee, C. Y.; Lee, J. W.; Ooi, Peck Toung (Veterinary Association Malaysia, 2013)
This study aimed to observe the effects of Escherichia coli (Neocoliporvaccine – Merial) vaccination on diarrhoea percentages, growth parameters (average weight per piglet and average daily gain) and mortality rate in new-born piglets. A field trial was conducted in 35 litters of piglets from gilts selected from a farm in Perak. They were randomly allocated into Treatment (16 litters from E. coli vaccinated gilts) and Control (19 litters) groups respectively. Body weights of the piglets were measured at days 1, 7, 14 and 21 of age and the episodes of diarrhoea and piglet mortality were monitored daily for each pen. The Treatment group had significantly lower Day 1 neonatal diarrhoea percentage (p < 0.05) and significantly lower mortality rate from Day 1 to Day 7. The total mortality rate for overall period of 1 - 21 days in the treatment group was at 3.90% when compared to the control group at 8.96%. However, there were no significant differences (p > 0.05)in the overall diarrhoea percentages (1 - 14 days) and weekly growth parameters between both groups. Environmental stress and inevitable routine treatment of diarrhoea with antimicrobials within the farm may have affected the significance of the diarrhoea percentages and growth parameters in this study. In conclusion, E. coli vaccination in gilts was shown to significantly reduce piglet mortality from Day 1 to Day 7 and neonatal diarrhoeal percentageson1-day-old piglets under typical farm conditions in this pilot study in Malaysia.